2020
DOI: 10.1007/s40430-020-02471-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental study on surface residual stress of ultra-precision turned 2024 aluminum alloy

Abstract: In order to reveal the influence of cutting parameters on the surface residual stress of 2024 aluminum alloy in ultra-precision cutting, the thermal coupling simulation of 2024 aluminum alloy ultra-precision cutting process was carried out based on ABAQUS software, and it was verified by the residual stress test of ultra-precision machined samples. The results show that the dominant factor of the machining residual stress of 2024 aluminum alloy ultra-precision with single crystal diamond tool is the plastic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, double-sided lapping has gradually been proposed to become one of the key processing methods in precision machining due to its high removal rate, excellent flatness, high parallelism and symmetrical stress introduction [4,5]. However, since the pure copper thin substrates are sensitive to stress, the performance stability of precision parts will be affected [6] and warping deformation may occur during the processing, resulting in deterioration of workpiece flatness. Some research showed that the factors causing workpiece deformation are related to the existence of initial residual stress and the introduction of machining stress [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, double-sided lapping has gradually been proposed to become one of the key processing methods in precision machining due to its high removal rate, excellent flatness, high parallelism and symmetrical stress introduction [4,5]. However, since the pure copper thin substrates are sensitive to stress, the performance stability of precision parts will be affected [6] and warping deformation may occur during the processing, resulting in deterioration of workpiece flatness. Some research showed that the factors causing workpiece deformation are related to the existence of initial residual stress and the introduction of machining stress [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al 15 developed a crystal plasticity finite element model (CPFE) for ultra-precision diamond cutting of polycrystalline copper, based on which the anisotropic machining characteristics, in terms of cutting force, machined surface morphology, and chip profile, are successfully captured. Liu et al 16 carried out a coupling thermal-mechanical FE simulation of ultra-precision cutting process of 2024 aluminum alloy, and showed that plastic deformation of workpiece dominates the machining residual stress. Tajalli et al 17 used the crystal plasticity (CP) theory to simulate the micro-machining process of face-centered cubic (FCC) metallic materials, and studied the effect of crystal orientation of the specimen on the cutting process.…”
Section: Introductionmentioning
confidence: 99%